2010
DOI: 10.1007/s00330-010-1778-7
|View full text |Cite
|
Sign up to set email alerts
|

Liver virtual non-enhanced CT with dual-source, dual-energy CT: a preliminary study

Abstract: VNCT(A) may potentially replace TNCT as part of a multi-phase liver imaging protocol with consequent saving in radiation dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(69 citation statements)
references
References 17 publications
4
63
1
1
Order By: Relevance
“…Moreover, the CNR was significantly higher in VNE images, and VNE images showed lower noise than TNE images, which was attributed to the noise reduction filter. Our results agreed with those of several previous studies in patients after endovascular aneurysm repair, patients with renal and adrenal masses, and patients with liver parenchymal lesions [19][20][21][22], demonstrating a comparable image quality of VNE images to that of TNE images. Therefore, if we omitted the acquisition of TNE images from our pancreatic protocol CT imaging, which was composed of pre-contrast, pancreatic and hepatic venous phase images, we could reduce approximately 14.14% (mean51.36 mSv) of the total radiation dose of our routine pancreatic protocol CT imaging (mean59.65 mSv).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the CNR was significantly higher in VNE images, and VNE images showed lower noise than TNE images, which was attributed to the noise reduction filter. Our results agreed with those of several previous studies in patients after endovascular aneurysm repair, patients with renal and adrenal masses, and patients with liver parenchymal lesions [19][20][21][22], demonstrating a comparable image quality of VNE images to that of TNE images. Therefore, if we omitted the acquisition of TNE images from our pancreatic protocol CT imaging, which was composed of pre-contrast, pancreatic and hepatic venous phase images, we could reduce approximately 14.14% (mean51.36 mSv) of the total radiation dose of our routine pancreatic protocol CT imaging (mean59.65 mSv).…”
Section: Discussionsupporting
confidence: 92%
“…Zhang et al (92) recently reported that the avoidance of non-contrast CT in a multiphasic CT protocol might reduce the radiation dose. De Cecco et al (93) reported similar findings, but they stated that an optimal virtual non-contrast image was only possible in patients with a low BMI.…”
Section: Gastrointestinal and Abdominal Applicationsmentioning
confidence: 99%
“…The effective dose ranges from 22.5 to 36.4 mSv and from 9.4 to 13.8 mSv for DECT and single-energy CT imaging, respectively. An increased radiation dose can be justified when unenhanced CT images are eliminated from the CT protocols, which may result in an overall radiation dose saving (92,93,105,106). Beam-hardening artifacts can be observed in thorax perfusion DECT due to the dense contrast in the superior vena cava, which can mimic an embolus.…”
Section: Limitations Of Dual-energy Mdctmentioning
confidence: 99%
“…To reduce errors stemming from the CT image noise, we generate a first-pass similarity matrix from a noisy CT image and suppress noise on the CT image by matrix multiplication shown in Eq. (9). An updated similarity matrix is then produced on the noise-suppressed CT image.…”
Section: B Penalized Weighted Least-square Optimization With Similmentioning
confidence: 99%
“…Dual-energy CT (DECT) has been increasingly used for iodine quantification, 1 kidney stone characterization, [2][3][4] virtual monochromatic imaging, 5,6 lung perfusion/ventilation studies, 7 and virtual nonenhanced images [8][9][10] among a growing list of diagnostic applications. However, material differentiation via DECT still suffers from noise amplification during the signal decomposition process.…”
Section: Introductionmentioning
confidence: 99%